1997
DOI: 10.1097/00000478-199709000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Glomus Tumor: A Case Report and Review of the Literature

Abstract: This report concerns a malignant glomus tumor, a rare soft tissue tumor that was examined immunohistochemically and ultrastructurally. It occurred in a 44-year-old male patient who had suffered from dull pain and stiffness in the right thigh for 10 months. Radiographic examination revealed a well-defined osteolytic lesion in the diaphysis of the right femur. Hypervascularity of the tumor was observed angiographically. Computed tomographic and magnetic resonance examinations showed an intramuscular mass invadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 19 publications
5
48
0
Order By: Relevance
“…Although glomus tumors are predominantly benign lesions, they occasionally may show atypical features including infiltrative growth pattern or multicentricity [11][12][13]. A small number of cases of glomus tumor have been reported as histologically malignant on the basis of morphological features including nuclear atypia, necrosis, and mitotic activity [11,14,15]. Only a few examples of metastatic disease have been described, and none of these involve sellar glomus tumors [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although glomus tumors are predominantly benign lesions, they occasionally may show atypical features including infiltrative growth pattern or multicentricity [11][12][13]. A small number of cases of glomus tumor have been reported as histologically malignant on the basis of morphological features including nuclear atypia, necrosis, and mitotic activity [11,14,15]. Only a few examples of metastatic disease have been described, and none of these involve sellar glomus tumors [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Masson [18]suggested that this tumor represented a hyperplasia or overgrowth of the glomus body. Glomus tumors are therefore usually benign, although malignant cases are occasionally reported [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…27 Glomus tumors are further classified into 3 categories, with regard to the proportions of glomus cells, vessels, and smooth-muscle components: the Glomus tumor proper type, with the round glomus cells representing the largest component; the glomangioma type, where vessels are predominantly present; and glomangiomyoma, where spindle cells are the predominant cell type. 29,30 An oncocytic type, where the tumor cells are characterized ultrastructurally by numerous closely packed round or ovoid mitochondria, has also been described. 13 The histologic criteria of malignancy in glomus tumors are deep location, size Ͼ 2 cm, presence of atypical mitotic figures, or a combination of moderate to high nuclear grade and Ն 5 mitotic figures per 50 high-power field.…”
Section: Discussionmentioning
confidence: 99%